2000
DOI: 10.1017/s1356186300011913
|View full text |Cite
|
Sign up to set email alerts
|

Dualism in Iranian and Christian Traditions

Abstract: Since the time when the human race first began to speculate about the origin of the universe there have been two cosmological models that have seemed particularly attractive to its imagination. One has been to derive everything in the world from a single primal origin, out of which the cosmos, in all its apparent complexity, evolves. The other has been to view the history of the universe as a battle between two opposing forces which contradict and undermine each other. The two views can be called monism and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…At one end of the spectrum of opinions, Widengren (, p. 149, following his teacher Nyberg , p. 416, , p. 373) concluded it was virtually certain that the Achaemenids were not Zoroastrians; at the other end, Duchesne‐Guillemin and Boyce concluded they were Zoroastrians, Shaked (, p. 90) believes the assumption that they were Zoroastrians is correct, while Schwartz () and Schmitt (, p. 424) appear to have taken it for granted that the Achaemenids were Zoroastrians. De Blois (, p. 3) even suggested that “Zoroastrianism was adopted as the state religion of the Achaemenid empire” (cf. Stausberg , p. 157).…”
Section: Were the Achaemenids Zoroastrians?—questions Of Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…At one end of the spectrum of opinions, Widengren (, p. 149, following his teacher Nyberg , p. 416, , p. 373) concluded it was virtually certain that the Achaemenids were not Zoroastrians; at the other end, Duchesne‐Guillemin and Boyce concluded they were Zoroastrians, Shaked (, p. 90) believes the assumption that they were Zoroastrians is correct, while Schwartz () and Schmitt (, p. 424) appear to have taken it for granted that the Achaemenids were Zoroastrians. De Blois (, p. 3) even suggested that “Zoroastrianism was adopted as the state religion of the Achaemenid empire” (cf. Stausberg , p. 157).…”
Section: Were the Achaemenids Zoroastrians?—questions Of Methodologymentioning
confidence: 99%
“…A special problem arose from the fact that about 490 BCE, the calendar known from post-Avestan Zoroastrian texts had been adopted in Cappadocia and, presumably, in the entire empire (de Blois 1996, Panaino 1990, pp. 665-66, 2010.…”
Section: Were the Achaemenids Zoroastrians?-questions Of Methodologymentioning
confidence: 99%
See 1 more Smart Citation